Time management analysis in engineering as a strategy for improving performance and reducing work stress - Rodríguez Rojas, Einer (2024)
Work stress has become one of the main health disorders worldwide. Daily occupations end up conditioning people to extend their working hours in order to fulfill their obligations. Important activities such as sharing with loved ones are relegated to the background. Physical problems, mental problems and problems in human relationships are just some of the consequences of being trapped in a circle of influence managed by stress. An alternative to reduce stress is to have greater availability of time, a valuable and unrepeatable resource that is possible to manage. The present research aims to provide options to manage time in a better way so that it finally translates into a decrease in stress. To comply with the study, a non-probabilistic convenience sample is used. Data collection is carried out using a predefined template. More than 1,300 data were generated that are processed using descriptive statistics to find possible time management patterns. When processing the data, a limitation to the study is identified that requires adjusting the model. The information can be subject to subjectivity, since the activity that for one individual may be contained in a classification, for another, the interpretation could be different. The conclusions suggest that the subjects of the study classify their activities as productive to a greater extent, however, not in all cases could they be classified as activities associated with medium-term objectives, many of them are governed by urgency and correspond to routine. The creation of habits and tools such as the ability to delegate are essential to accomplish tasks.